Profesor Stanisław Kurnatowski (1929-2015). Interdysciplinarny wymiar archeologii - Mamzer, Henryk (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2015)
In this farewell speech for Professor Kurnatowski, I would like to emphasize that he was a master and a teacher, the epitome of a researcher and a model to follow. Professor Kurnatowski was a reflexive researcher, or rather a thinker, close to a philosopher. He would go far beyond conventional archaeology, focusing on the historical process, starting in the early bronze age until the Middle Ages. The attempt at presenting Professor Stanisław Kurnatowski as a researcher is an attempt at showing “the way we could be”.